SYSTEMATIC LITERATURE REVIEW: KEPUASAN PASIEN TERHADAP LAYANAN KESEHATAN DI PUSKESMAS - Prita Devy Igiany (Program Studi Perekam Medis & Informasi Kesehatan, 2022)
The public health center is a first-level health service facility that provides health service facilities with the hope of providing service activities for the community in accordance with their duties and authorities. Health institutions must pay attention to the quality of their services because it can affect the level of patient satisfaction. Patient satisfaction is the level of patient feeling that arises as a result of the performance of the healthcare facility they get after compares with what they expect. Therefore, patient satisfaction is an important thing to determine the success of services in health care facilities. Patient satisfaction is related to the dimensions of the level of service quality through five aspects (reliability, responsiveness, assurance, empathy, and tangible). This type of research is a systematic review that is carried out by collecting, selecting, extracting, and reviewing scientific articles that have topics relevant to the research objectives. The number of articles used in this study was 13 articles published from 2014-2022. Based on the results of the study, the average patient satisfaction with registration services at the public health center based on the tangible dimension was 85.51%, the reliability dimension was 86.51%, the responsiveness dimension was 78.34%, the assurance dimension was 78.02%, and the empathy dimension by 77.43%. It can be seen that the dimension of service quality that most dominantly affects patient satisfaction is the tangible dimension (physical evidence) with the highest percentage.